Economic and Social Impacts of Industry 4.0 on Chemical Companies in the Czech Republic - Oskar BAKES; Jan VAVRA; Jana KOSTALOVA (Communications of International Proceedings, 2021)
Technological development is changing the form of production and, with it, the role and requirements for employees. This trend is connected with the concept of Industry 4.0, also referred to as the Fourth Industrial Revolution. However, the concept is often described in a broad perspective and the specifics of individual industries are often overlooked. This article deals with Industry 4.0 and its impacts on Czech chemical companies. First, the very concept of Industry 4.0 is defined, followed by definitions of the technological elements of the concept and related socio-economic aspects thereof. Special emphasis is placed on research issues related to changes in competencies and requirements for employees. The results not only summarise state of implementation of Industry 4.0 in the chosen companies but also bring out new research opportunities and furthermore show gaps in current conception of Industry 4.0 by academics – contrary to conception in practice.
Keywords: Industry 4.0; chemical manufacturing companies; job positions; Technology 4.0; Competencies 4.0